Prognostic relevance of palliative primary tumor removal in 37,793 metastatic colorectal cancer patients: a population-based, propensity score-adjusted trend analysis - Tarantino, Ignazio; Warschkow, René; Worni, Mathias; Cerny, Thomas; Ulrich, Alexis; Schmied, Bruno; Güller, Ulrich (Annals of surgery, 2015)
Objective: To assess whether palliative primary tumor resection in colorectal cancer patients with incurable stage IV disease is associated with improved survival. Background: There is a heated debate regarding whether or not an asymptomatic primary tumor should be removed in patients with incurable stage IV colorectal disease. Methods: Stage IV colorectal cancer patients were identified in the Surveillance, Epidemiology, and End Results database between 1998 and 2009. Patients undergoing surgery to metastatic sites were excluded. Overall survival and cancer-specific survival were compared between patients with and without palliative primary tumor resection using risk-adjusted Cox proportional hazard regression models and stratified propensity score methods. Results: Overall, 37,793 stage IV colorectal cancer patients were identified. Of those, 23,004 (60.9%) underwent palliative primary tumor resection. The rate of patients undergoing palliative primary cancer resection decreased from 68.4% in 1998 to 50.7% in 2009 (P < 0.001). In Cox regression analysis after propensity score matching primary cancer resection was associated with a significantly improved overall survival [hazard ratio (HR) of death = 0.40, 95% confidence interval (CI) = 0.39-0.42, P < 0.001] and cancer-specific survival (HR of death = 0.39, 95% CI = 0.38-0.40, P < 0.001). The benefit of palliative primary cancer resection persisted during the time period 1998 to 2009 with HRs equal to or less than 0.47 for both overall and cancer-specific survival. Conclusions: On the basis of this population-based cohort of stage IV colorectal cancer patients, palliative primary tumor resection was associated with improved overall and cancer-specific survival. Therefore, the dogma that an asymptomatic primary tumor never should be resected in patients with unresectable colorectal cancer metastases must be questioned.
Gesehen am 29.06.2020